2021
DOI: 10.1152/jn.00561.2020
|View full text |Cite
|
Sign up to set email alerts
|

The detailed organization of the human cerebellum estimated by intrinsic functional connectivity within the individual

Abstract: Distinct regions of the cerebellum connect to separate regions of the cerebral cortex forming a complex topography. While cerebellar organization has been examined in group-averaged data, study of individuals provides an opportunity to discover features that emerge at a higher spatial resolution. Here functional connectivity MRI was used to examine the cerebellum of two intensively-sampled individuals (each scanned 31 times). Connectivity to somatomotor cortex showed the expected crossed laterality and topogra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 86 publications
(217 reference statements)
6
79
0
Order By: Relevance
“…Electric stimulation during neurosurgery demonstrated that the movements of the face and mouth are primarily represented in the hemispheric lobule VI (Mottolese et al, 2013). A recent high-resolution study on two individual subjects, investigating the functional connectivity between the cerebrum and the cerebellum using resting-state FMRI, corroborated this result (Xue et al, 2021). A graph theoretical analysis further elucidated the critical role of hemispheric lobule VI in the speech production network (Simonyan and Fuertinger, 2015).…”
Section: Areas Of Increased Brain Activitymentioning
confidence: 78%
“…Electric stimulation during neurosurgery demonstrated that the movements of the face and mouth are primarily represented in the hemispheric lobule VI (Mottolese et al, 2013). A recent high-resolution study on two individual subjects, investigating the functional connectivity between the cerebrum and the cerebellum using resting-state FMRI, corroborated this result (Xue et al, 2021). A graph theoretical analysis further elucidated the critical role of hemispheric lobule VI in the speech production network (Simonyan and Fuertinger, 2015).…”
Section: Areas Of Increased Brain Activitymentioning
confidence: 78%
“…Cerebellar injury shows poor visuospatial skills. Resting-state functional connectivity studies show the connection between the cerebellum and the parietal lobe involved in visuospatial integration ( 58 ). The cerebellum may contribute to figuring organization to promote effective visuospatial integration and perception while encoding shapes.…”
Section: Clinical Application Of Complex Figure Testmentioning
confidence: 99%
“…The results showed that the pattern of activity in rostrolateral prefrontal cortex distinguished individuals who rely on relative uncertainty for their exploratory decisions versus those who do not. Another recent study (Xue et al 2021) used functional connectivity MRI to examine the cerebellum of two intensively-sampled individuals (each scanned 31 times) and found idiosyncratic spatial details between these subjects. Hilt et al (2020) addressed the issue of how individual motor styles are dealt with during action observation.…”
Section: Mechanistic Basesmentioning
confidence: 99%